PERSEPSI PETANI ANGGOTA P3A TERHADAP PENGELOLAAN IRIGASI USAHATANI PADI SAWAH DI KELURAHAN MARGODADI KECAMATAN METRO SELATAN KOTA METRO - Armia, Nadia Ulfa; Gultom, Dame Trully; Effendi, Irwan (Lampung University, 2020)
This study aims to determine the perceptions of P3A member farmers on irrigation management of rice farming and to analyze the factors related to the perception of the farmers on irrigation management of rice farming. This research was carried out in Margodadi Village South Metro Subdistrict Metro Regency with 65 respondents from P3A members participating in P3A activities. Data were collected through a survey method and analyzed descriptively and using nonparametric statistical tests of Spearman Rank Correlation. The results of this study indicated that the perceptions of P3A member farmers on irrigation management of rice farming is in the medium category. Factors related to the perceptions of P3A member farmers on irrigation management of rice farming are formal education, motivation, needs, rice farming experience, knowledge, social environment, support of related agencies, and land size. Meanwhile, unrelated factors are age and number of dependents.Key words: field irrigation management, perceptions, P3A